Development of Electromobility in Terms of Freight Transport - Cempírek Václav; Rybicka Iwona; Ljubaj Ivica (Logi, 2019)
The paper deals with specific aspects regarding the current development trends of electromobility in the context of road freight transport. The current system of electric vehicles for road freight transport and the relevant investigations are based on the experience with operating trolleybuses, which have the same power supply of traction motors from the overhead traction line by means of traction pantographs. As for the future, it has not been decided yet which electromobility-related power system will be used in practice, whether the supply of electric motors from traction lines or battery packs. In the introductory chapters, the manuscript discusses the fundamental information regarding the electromobility, current projects dealing with this issue, individual aspects and attributes related to these existing power systems, and their advantages and disadvantages in terms of their usage. In the most important part of the manuscript, the adequate evaluation is performed, as well as very recommendations for future research in a given topic are proposed.